A novel mesoporous hydrogen-bonded organic framework with high porosity and stability. Issue 1 (2nd December 2019) - Wang, Bin; Lv, Xiu-Liang; Lv, Jie; Ma, Li; Lin, Rui-Biao; Cui, Hui; Zhang, Jian; Zhang, Zhangjing; Xiang, Shengchang; Chen, Banglin
Abstract : A highly chemically and thermally stable mesoporous hydrogen-bonded organic framework with a high surface area and a large pore volume has been rationally designed and constructed. Abstract : A highly stable hydrogen-bonded organic framework, HOF-14, has been successfully constructed and structurally characterized. It possesses a permanent three dimensional (3D) porous structure. The activated HOF-14 has a high BET surface area of 2573 m 2 g −1 and a record large pore volume of 1.36 cm 3 g −1 among HOF materials. In addition, HOF-14 also exhibits high chemical and thermal stability and is capable of highly selective separation of light hydrocarbons under ambient conditions.